Fucosylation and Sialylation of Fc-Fragment of anti-Tumour Necrosis Factor Alpha Antibodies do not Influence Their Immunogenicity in Monocyte-Derived Dendritic Cells. (26th February 2021) - Wawrzyniak, Marcin; Morsy, Yasser; Mladenov, Radoslav; Tontodonati, Giulia; Turgay, Yagmur; Herwig, Stefan; Back, Jonathan; Mally, Manuela; Faridmoayer, Amirreza; Scharl, Michael
Abstract: Background and Aims: Antibodies targeting tumor necrosis factor-alpha [TNF-alpha] are a mainstay in the treatment of inflammatory bowel disease. However, they fail to demonstrate efficacy in a considerable proportion of patients. On the other hand, glycosylation of antibodies might influence not only their immunogenicity but also their structure and function. We investigated whether specific glycosylation patterns of the Fc-fragment would affect the immunogenicity of anti-TNF-alpha antibody in monocyte-derived dendritic cells. Methods: The effect of a specific Fc-glycosylation pattern on antibody uptake by monocyte-derived dendritic cells [mo-DCs] and how this process shapes the immunologic profile of mo-DCs was investigated. Three N-glycoforms of the anti-TNF-alpha antibody adalimumab, that differed in the content of fucose or sialic acid, were tested: [1] mock treated Humira, abbreviated 'Fuc-G0', where the N-glycan mainly consist of fucose and N-acetylglucosamine [GlcNAc], without sialic acid; [2] 'Fuc-G2S1/G2S2' with fucose and alpha 2, 6 linked sialic acid; and [3] 'G2S1/G2S2' with alpha 2, 6 linked sialic acid, without fucose. Results: Our data demonstrated that neither fucosylation nor sialylation of anti-TNF-Abs [Fuc-G0, FucG2S1/G2S2, G2S1/G2S2] influence their uptake by mo-DCs. Additionally, none of the differentially glycosylated antibodies altered CD80, CD86, CD273, CD274 levels on mo-DCs stimulated in with lipopolysaccharide in the presence of antibodies. Next, we evaluated the levels of cytokines in the supernatant of mo-DCs stimulated with lipopolysaccharide in the presence of Fuc-G0, Fuc-G2S1/G2S2 or G2S1/G2S2-glycosylated anti-TNF antibodies. Only IL-2 and IL-17 levels were downregulated, and IL-5 production was upregulated by uptake of Fuc-G0 antibodies, as compared to control without antibodies. Conclusions: The specific modification in the Fc-glycosylation pattern of anti-TNF-alpha Abs does not affect their immunogenicity under the tested conditions. As this study was limited to mo-DCs, further investigation is required to clarify whether Ab uptake into mo-DCs might change the immunological profile of T- and B-cells, in order to ultimately reduce the formation of anti-drug antibodies and to improve the patient care.